Dvigatel'naya struktura sportivnoi bor'by s tochki zreniya teorii deyatel'nosti - Piloyan, R. A.; Shakhmuradov, Yu. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to substantiate the methodology of researches on the problem of wrestling technique's and tactic's essence. As the result of the theoretical investigation it had become possible to state, that existing methods of the sports motor structures have the serious limitations in the contemporary theory of physical education. The authors offer to use for these aims the psychological theory of activities, supplemented by the knowledges contained in the theory and practice of sport. The authors pretend to reveal the content of the sports wrestling as theactivities, to understand the mechanisms of the higher sports mastery' forming, to offer the incontradictory definition of the technique's and tactic's concepts.